Histórias e memórias - reconstruindo o lugar do campo na comunidade de São Sebastião - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The purpose of this article was to rescue the memories and stories of the people who constitute what is the town of São Sebastião. It was divided into three axes: Knowing the history of the village community of São Sebastião, rescuing the knowledge and knowledge from the memories that make up the community and understanding how the process of (re) signification of knowledge takes place generations. In order to do so, bibliographical research was carried out, and a rescue of the memories of the people who constitute the community of São Sebastião was carried out. Two moments were used: listening and narrative of memories. In summary, the research was based on the coexistence / observation and dialogue with the community, for even being part of this place often did not perceive the knowledge that gives identity to Saint Sebastian, which I am calling meaning and (re) signification knowledge.
Stories and memories - rebuilding the place of the field in the community of São Sebastião
Keywords: Educação do Campo; Memórias; Histórias; Field Education; Memories; Stories; CNPQ::CIENCIAS SOCIAIS APLICADAS